A filarial parasite potentially associated with the health burden on domestic chickens in Japan - Hayashi, Naoki; Hosokawa, Kumiko; Yamamoto, Yu; Kodama, Sachiko; Kurokawa, Aoi; Nakao, Ryo; Nonaka, Nariaki (Scientific reports, 2024)
Chickens in free-range environments are at risk of exposure to various pathogens, such as filarioids transmitted via hematophagous vectors. However, the study of filarioids in poultry has been largely neglected compared to the extensive studies focused on viruses, bacteria, and protozoa. Here, we performed histological and molecular investigations of the filarioids detected in domestic chickens from two different flocks in Hiroshima Prefecture, Japan. In the first case, adult worms were present in the pulmonary artery and right ventricle, and microfilariae were present in multiple organs of deceased chickens. In the second case, similar filarioids were detected in the organs and blood of one necropsied layer. Phylogenetic analysis using 18S rRNA gene fragments positioned the filarioid in the same clade as that of Onchocercidae sp., previously identified in a deceased chicken from Chiba Prefecture, Japan, that is located 500 km away from Hiroshima Prefecture. Based on 28S rRNA and mitochondrial COI gene fragments, the filarioid was positioned distinctly from previously reported genera of avian filarioids. These results suggest that the filarioids are potentially associated with the health burden on domestic chickens and belong to the genus Paronchocerca . Furthermore, we developed a nested PCR assay targeting mitochondrial COI and detected the parasite DNA from the biting midge Culicoides arakawae captured near the flock, suggesting that it serves as a vector. Our findings fill the knowledge gap regarding avian filarioids, laying the groundwork for future studies examining the epidemiology, life cycle, and species diversity of this neglected parasite group.